2021
DOI: 10.17478/jegys.862904
|View full text |Cite
|
Sign up to set email alerts
|

Examining the stress, depressive thoughts, and working memory capacities of the university students

Abstract: The objective of the study is to measure the capacity of the working memory, and also to investigate its relationship to life stress and depressive thoughts. The study sample consisted of 50 college students studied on Science and Art major. A cognitive task was designed to measure the working memory capacity based on the determinants found in previous research. The results indicated that there were statistically significant differences in the level of life stress events (high/low) on the task of measuring the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…For example, the study by Klein and Schwartz (1979) also found no significant gender differences in memory performance after training in sequential auditory memory. Similarly, recent studies have shown no gender differences in working memory performance (Hirsch et al, 2019) or in the effects of working memory training on cognitive performance (Abo Hamza and Helal, 2021;Abushalbaq et al, 2021;Liu et al, 2021).…”
Section: Lack Of Gender DI Erencesmentioning
confidence: 83%
See 2 more Smart Citations
“…For example, the study by Klein and Schwartz (1979) also found no significant gender differences in memory performance after training in sequential auditory memory. Similarly, recent studies have shown no gender differences in working memory performance (Hirsch et al, 2019) or in the effects of working memory training on cognitive performance (Abo Hamza and Helal, 2021;Abushalbaq et al, 2021;Liu et al, 2021).…”
Section: Lack Of Gender DI Erencesmentioning
confidence: 83%
“…This notion has a substantial effect on both the instructor and the learner (Trinidad, 2020). Modern cognitive theory emphasizes the interrelation of attention, perception, working memory, and longterm memory in education (Chang et al, 2019;Cicekci and Sadik, 2019;Cortés Pascual et al, 2019;Lodge and Harrison, 2019;Abo Hamza and Helal, 2021;Abushalbaq et al, 2021;Berkowitz et al, 2022). Attention serves as the primary cognitive filter for external inputs, impacting perception and learning (Lodge and Harrison, 2019).…”
Section: Cognition and Memory In The Context Of Educational Psychologymentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive failures can be caused by a variety of factors, including fatigue, stress, and mental health issues. For example, a studies found that stress and anxiety were associated with working memory deficits and poor academic performance in university students (Abbasi et al, 2021;HELAL & ABO HAMZA, 2021;Omary & Persky, 2019). Similarly, a studies found that academic motivation and study behavior had a stronger effect on academic achievement than cognitive factors such as working memory and attentional control (Pascoe et al, 2018;Shi & Qu, 2022) Both psychological defeat and cognitive failure can contribute to academic failure for university students, but psychological defeat may have a stronger impact (Gilar-Corbi et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%